2012
DOI: 10.1080/15700763.2011.577926
|View full text |Cite
|
Sign up to set email alerts
|

Leading the Ongoing Development of Collaborative Data Practices: Advancing a Schema for Diagnosis and Intervention

Abstract: Research suggests that school leaders play an important role in cultivating and developing collaborative data practices by teachers. Although diagnosis and intervention are critical facets of leaders' work to support collaborative data practice development, this work remains poorly understood. Missing from data-use literature is more explicit and holistic attention to diagnostic factors and interventions of importance to the ongoing development of collaborative data practices. To address this knowledge gap, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 85 publications
0
61
0
Order By: Relevance
“…Once again, other studies of data use also indicate that district-level conditions can influence CBI-teacher work, including structures that support a data-use initiative, leadership, funding, and intervention alignment with other policies (Farrell, in press;Marsh, 2012). Principal commitment, strategic selection of participants, and resources of time, space, and funding are other school-level factors that our research and other studies have found to enable CBI efforts (Cosner, 2012;Levin and Datnow, 2012).…”
Section: Conditions That Moderated the Capacity-building Processmentioning
confidence: 93%
“…Once again, other studies of data use also indicate that district-level conditions can influence CBI-teacher work, including structures that support a data-use initiative, leadership, funding, and intervention alignment with other policies (Farrell, in press;Marsh, 2012). Principal commitment, strategic selection of participants, and resources of time, space, and funding are other school-level factors that our research and other studies have found to enable CBI efforts (Cosner, 2012;Levin and Datnow, 2012).…”
Section: Conditions That Moderated the Capacity-building Processmentioning
confidence: 93%
“…A common "mantra" of the modern day educator (Ikemoto & Marsh, 2007; see also Coburn & Turner, 2011Hamilton et al, 2009;Mandinach, 2012), being "data driven" is not only an expectation, but also increasingly a formal criteria used in teacher evaluations. Yet, research suggests that although teachers appreciate having access to various types of dataincluding metrics from classroom assessments, common grade assessments, teacher observations, interim or benchmark assessments, state tests-they often struggle to use data due to a lack of skills and knowledge to formulate questions, select indicators, interpret results, and develop instructional responses (Cosner, 2012;Kerr et al, 2006;Means, Chen, DeBarger, & Padilla, 2011;Olah, Lawrence, & Riggan, 2010;Supovitz & Klein, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, much quality work has emerged recently that focuses on what colleges of education (and nontraditional preparation programs) do, can do, or should do to better prepare ECT to use data in the service of teaching and learning (Mandinach & Gummer, 2013;Mandinach & Jackson, 2012). And, some research on district-enacted supports (i.e., data teams, instructional/data coaches, and collaboration) provides a strong and growing evidence base to guide district efforts (see Anderson, Leithwood, & Strauss, 2010;Cosner, 2012;Kerr, Marsh, Ikemoto, Darilek, & Barney, 2006;Means et al, 2011).…”
Section: Mentors As Supports Formentioning
confidence: 98%